GRP014 Closing the gap ñ improving patient safety with better drug information. Issue 2 (12th March 2012) - Mildner, C.; Degenhardt, C.; Lamberth, C.; Metzel, R.; Witte, J.; Krämer, I.
Abstract : Background: The problem of poor information transfer exists at the interface between clinical and ambulatory treatment. Patients are not sufficiently informed about their current and future drug treatment. Purpose: To compare knowledge of medicines to be managed at discharge with or without the involvement of a clinical pharmacist. Materials and methods: The amount and depth of information given to the patients about drug treatment started during hospital with and without the intervention of clinical pharmacists were investigated consecutively in a controlled, comparative study at five different hospitals (11 wards). The satisfaction of patients and their general practitioners (GP) with the different style of discharge management was investigated by means of questionnaires. Results: In phase 1 (no involvement of a clinical pharmacist, 847 patients) approximately 50% of patients were prescribed new drugs which were recommended to be continued after discharge. 12% of these patients were not instructed in hospital or in outpatient settings about their newly-prescribed medicines. Even if they were informed about their medicines, 22% of patients were not, or only partially, satisfied. In phase 2 (617 patients), all patients were trained in using their newly-prescribed medicines, so the information ratio rose to 100%. Patient satisfaction regarding the quality of education increased to 89%. Each patient got an illustrated patient-specific medicines plan, which was reported to be helpful by more than 80% of patients. GPs confirmed that their patients were better informed (36% improvement) thus reducing their effort (22% less GP effort required). Conclusions: By involving clinical pharmacists, the gap in patients' knowledge about their medicines was reduced. GPs found their patients better informed and appreciated the reduced time and effort.